Marine geology data accessibility in the European Framework: The I.G.M.E. participation in the GEO-SEAS project. - Zananiri, Ι.; Mitropoulos, D.; Zimianitis, V.; Ioakim, Chr.; Papadopoulos, V.; Efthimiou, G. (Bulletin of the Geological Society of Greece, 2013)
During more than 30 years of activity and participation in numerous research projects, the Institute of Geology and Mineral Exploration of Greece has carried out extensive work in marine geology and a vast amount of data has been collected. In order for those data to be available and used by the international scientific community, a need for standardization and harmonization was imminent. Towards this scope IGME, along with 25 other marine geological and geophysical data centres, located in 17 European maritime countries, participated in the GEO-SEAS project: the implementation of an e-infrastructure. The aim of the project was to enable users to identify, locate and access pan-European, harmonised and federated marine geological and geophysical datasets and derived data products held by the data centres through a single common data portal. All available data have been harmonized according to the GEO-SEAS guidelines and standards. Detailed metadata files were created, accompanied by the corresponding data and additional information files. The standardization, harmonization and provision of data and metadata, carried out through the GEO-SEAS project, are aligned with European directives and recent large-scale framework programs on global and European scales.